Factors influencing training competencies of oncology nurses: A systematic review - Brigitta Armelia Mairuhu; Enjelika Putri Manalu; Erica Dorelia Pajuk; Kyela Friska Br Sinurat; Ni Gusti Ayu Eka (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Oncology nursing requires specialized knowledge and skills to provide optimal care for cancer patients. Training and continuous professional development are essential to ensure high-quality patient care. However, various factors may influence nurses' participation and effectiveness in training programs, including institutional support, accessibility to training, individual motivation, and workplace challenges. Understanding these factors is crucial for improving oncology nursing competencies Purpose: To map the factors that influence oncology nurses' training competence in oncology services. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Oncology nurses, I: Training and competency development programs, C: compared with those who did not receive or with a variety of training methods, O: Had an impact on competency improvement, S: Randomized controlled trials. The article search was conducted systematically using the keywords: “Nurses,” AND “Nursing Staff,” AND “Registered Nurses,” AND “Oncology Nursing,” AND “Motivation,” AND “Motivational Factors,” AND “Education,” AND “Training Programs” AND “Oncology Service,” AND “Hospital,” AND “Cancer Care Units”. Results: Effective CPD is contextually relevant, culturally aligned, and uses active learning strategies to develop both technical and non-technical skills, with leadership support and clear career pathways further reinforcing competency growth. Conclusion: Oncology nursing competencies improve most effectively through well-structured, adaptive CPD programs reinforced by committed institutional leadership.